(untitled) (Andamios, Revista de Investigación Social, 2015)
The article deals with the treasure of duendes as a common folk myth that generated a lexicalizacion and proverb, which has numerous allusions and quotations from literary sources, in particular in the Siglo de Oro. Both speeches are compared in the light of the concepts of iconotropisme (Graves) and gift (Mauss), which leads to a hermeneutics and deconstruction of the concept of treasure in these sources, with emphasis on the description of metonymic movement and the opening of the meaning. The literaturising of the folktale culminates in a process of semantic restriction, where treasure is materialized in a unidirectional way and simultaneously moralize as source of deception. On the other hand, the classical concept of agalma is much more all-inclusive view and appearance play a large role, shaping as an isotopy of the visionary and the visibility, which engages well two worldviews. The symbolic devaluation of the gift explains the use of the proverb in the Siglo de Oro.